THE EFFECTS OF SCHOOL SELF-EVALUATION, QUALITY POLICY, QUALITY PLANNING, AND QUALITY IMPROVEMENT ON QUALITY ASSURANCE OF STATE JUNIOR SECONDARY SCHOOLS IN JAKARTA - Efendi, Muhamad; Suryadi, Suryadi; Akbar, Ma’ruf (JERAM, 2018)
THE EFFECTS OF SCHOOL SELF-`EVALUATION, QUALITY POLICY, QUALITY PLANNING, AND QUALITY IMPROVEMENT ON QUALITY ASSURANCE OF STATE JUNIOR SECONDARY SCHOOLS IN JAKARTA MUHAMAD EFENDI Education Management Study Program, postgraduate faculty, State University of Jakarta, Indonesia   ABSTRACT The purpose of this study is to find out the effects of school self-evaluation, quality policy, quality planning, and quality improvement on the quality assurance of State Junior Secondary Schools in Jakarta. The population of this study is two hundred and eighty nine state junior secondary schools. Empirical data was drawn from the research sample were collected by using questionnaires that have been checked for validity and reliability distributed to one hundred and sixty five state junior secondary schools. The data was analyzed using statistical package for social science (SPSS V.20) and Microsoft Excel package and it was presented in tables and bar graphs. The results of this study revealed: 1) Three factors have a significant direct positive effect on quality assurance are quality policy, quality planning, and quality improvement of State Junior Secondary Schools in Jakarta. 2) School self-evaluation has a significant direct positive effect on quality policy, quality planning, and quality improvementof State Junior Secondary Schools in Jakarta.3) The Quality policy has a significant direct effect on quality planning, and quality planning has a significant direct effect on quality of State Junior Secondary Schools in Jakarta. The researcher recommended the deployment of a culture of school self-evaluation activities, and all stakeholder play an active role in supporting the quality policy established by the school leadership and implement the quality plan as planned and educators to always improve the quality of learning and teaching in order to improve the quality of education in school. Keywords:  Quality assurance, School Self-evaluation,   Quality policy,   Quality planning, Quality improvement.